The Impact of Liaison and Support on the Teaching of Hungarian and Language Maintenance in the Diaspora: A Case Study of Brazil and Chile - Thomázy Gabriella; Thomázy Timea (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-"RIK-U" Kft., 2020)
Abstract. A significant number of Hungarian minorities live in South America. Brazil and Chile are two countries where a large number of Hungarians arrived in several immigration waves, mostly between and after the two World Wars and after the Hungarian Revolution of 1956. Whereas Brazil's Hungarian minority is currently mainly concentrated in São Paulo (80%), Chilean Hungarians are found relatively isolated, in smaller groups. Furthermore, there was no Hungarian Embassy in Chile for a long time. The goal of the present paper is to give an overview about the situation of the Hungarian language teaching in two South American countries, Brazil and Chile. This paper also touches upon the language policy of these countries, the institutional support system gained for the vitality of the minority language and review the bilateral cooperation (between the home country and the diaspora) for language maintenance and language revitalization.

Dél-Amerikában jelentős számú magyar kisebbség él. Brazília és Chile két olyan ország, ahová több kivándorlási hullámban, de főleg a két világháború között és azt követően, valamint az 1956-os forradalom után érkeztek jelentős számban magyarok. Míg Brazília magyar kisebbsége jelenleg főként São Paulo városában összpontosul (80%), addig Chilében, viszonylag elszigetelten, kisebb csoportokban élnek a magyarok, továbbá hosszú ideig magyar nagykövetség sem volt az országban. Jelen cikk célja, a két dél-amerikai ország, Brazília és Chile magyar nyelvoktatási helyzetének bemutatása, ide sorolható az adott ország nyelvpolitikája, a kisebbségi nyelv vitalitását segítő intézményrendszere, valamint a nyelvmegtartás, illetve a nyelv revitalizációja érdekében folyó kétoldalú munka (anyaország-diaszpóra) bemutatása.

Резюме. У Південній Америці проживає доволі чисельна угорська діаспора. Бразилія та Чилі – це дві держави, до яких було кілька хвиль еміграції, переважно угорці виїжджали сюди в період між двома світовими війнами та після революції 1956 року. Якщо в Бразилії угорська діаспора зосереджена в місті Сан-Паулу (80%), то в Чилі угорці проживають у порівняно ізольованих, невеликих групах. Крім цього, у цій країні довгий час не було посольства Угорщини. Мета цієї публікації – простежити ситуацію з вивченням угорської мови у двох південноамериканських країнах – Бразилії та Чилі, зокрема охарактеризувати мовну політику цих держав, систему інституцій, які мають підтримувати мови меншин, а також двосторонню (материнська держава – діаспора) роботу з метою збереження мови та її ревіталізації.
A kapcsolattartás és a támogatás hatása a diaszpórában élők magyar nyelvoktatására és nyelvmegőrzésére – Brazília és Chile. Esettanulmány
Вплив налагоджених зв’язків та наданої підтримки на вивчення та збереження в діаспорі угорської мови: приклади Бразилії та Чилі
https://kmf.uz.ua/wp-content/uploads/2021/10/limes-2020-issue-vii_volume-2.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008907
Keywords: Hungarian minority; heritage language; Brazil; Chile; language policy; education